Implementation of Data Security Framework in Microservices Cloud Computing Architecture for E-Learning Platform - Fika Ulfa Widowati (International Journal of Management Science and Information Technology, 2026)
Secure cloud infrastructure is necessary for Indonesia's e-learning to undergo a digital transition. This study examines how a data security framework is implemented on a microservices architecture based on Platform-as-a-Service (PaaS). Using a kualitatif approach through case studies, this study integrates the principles of Arsitektur Zero Trust, end-to-end encoding, and service isolation. According to the research findings, this integrated framework can enhance system resilience, speed up security incident response by 65%, and lower the chance of data breaches by up to 87%. The PaaS model's high scalability and inadequate resource control make this framework easily applicable to a variety of other large-scale digital platforms. When creating an e-learning ecosystem that is resistant to cyberattacks, developers and educational institutions can use this research as a strategic guide.